Alternativas para la conservación de fuentes naturales de agua dulce de la microcuenca del Río Chillayacu, perteneciente al cantón Chilla - Yanez Maldonado, Gina Esthefanía (2015)
In Ecuador there are highly agricultural provinces, and one of them is the province of El Oro, biodiverse industry supported by various natural factors especially water, from the highest slopes of the province. Today the demand for water is declining by different human activities of man, causing damage to nature. These cases have been observed in the Chilla Canton where deforestation, misuse of water, agricultural frontier expansion, etc., has caused strong negative changes to the river Chillayacu who is the main tributary to this sector. Whereas the management of this watershed is vital for the inhabitants of Chilla, this research is the first conducted through a field diagnosis expects to generate a proposal to serve as basis for the municipality take decisions aimed at rational use and sustainable watershed resources. The mechanisms of Payments for Environmental Services (PES) for watershed conservation are part of this approach, which aims to provide quality water through conservation and watershed rehabilitation, the aim of this proposal is the implementation of a methodological payment system for environmental water services and develop a proposal for the conservation and protection of the river watershed Chillayacu. In developing the proposal the components, the phases and logistical resources to implement the PSA response system and product conservation and protection of the watershed indicated. Then the proposal through feasibility analysis where the technical, economic, social and environmental aspects, obtaining the conclusion that the proposal will generate a better quality and quantity of water and also restore flora resources, wildlife and landscape was valued explained.